(untitled) (Journal of the Bangladesh Agricultural University, 2012)
Practical methods for the accurate estimation of water requirement for irrigated agriculture are essential. Simulation model is a useful tool to estimate water balance in the crop field. In this study, the BUDGET model was used to evaluate its performance to simulate water balance in wheat field. The BUDGET model is composed of a set of validated subroutines describing the various processes involved in water extraction by plant roots and soil water movement in absence of a water table. The model was run to simulate evapotranspiration values with the actual observed weather, crop and soil data for three years (2002-2005), obtained from experimental Station of Bangladesh Institute of Nuclear Agricultural (BINA). The input data of model are separated into four stages and the value of Kc and root depth are different for each stage. Evaluation of model performance is done with both graphical display and statistical criteria. The simulated values fall close to 1:1 line, indicating better performance. The statistical parameters such as standard deviation (SD), standard error (SE), coefficient of variation (CV) of simulated and actual evapotranspiration values are found 21.07 and 29.23; 4.49 and 6.23; and 38.03 and 50.75, respectively. Both the standard error and coefficient of variation for simulated values are found lower than the observed values indicating stability of the model output. The coefficient of determination value (R2 =0.83) is high for this model, which indicates good simulation performance. The relative error (RE) is 23.28 percent and model efficiency (EF) is 78.95 percent which means that the simulation of actual evapotranspiration is satisfactory. The value of Index of agreement (IA) is 0.918 which indicates a very good performance of the model. The overall statistical parameters of simulation period are in satisfactory level. Therefore, the BUDGET model is able to predict actual evapotranspiration for any level of soil moisture with reasonable accuracy. The model can be used in planning, management and operation of an irrigation project for judicious use of water with the limited inputs, especially suitable for countries where modeling of crop yield is needed under water stress conditions. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11038 J. Bangladesh Agril. Univ. 9(2): 257266, 2011